2018
DOI: 10.1007/s12020-018-1633-1
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and management of postoperative hyperglycemia in patients undergoing insulinoma resection

Abstract: Hyperglycemia is common after insulinoma resection, and a subset of patients require transient treatment with insulin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 15 publications
0
14
0
2
Order By: Relevance
“…22 Although its duration and significance in human medicine is unclear, most studies suggest it is usually transient and self-resolves in 3 to 9 days. 18 In a recent study in people, the prevalence of hyperglycemia was 36%, 24 and no significant difference in age, sex, tumor size, or surgical approach were noted between human patients with normoglycemia and those that were hyperglycemic during the postoperative period. 24 In dogs, postoperative transient hyperglycemia has been commonly recognized, and it has been associated with a better prognosis, 12 whereas the development of permanent DM is believed to be uncommon.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…22 Although its duration and significance in human medicine is unclear, most studies suggest it is usually transient and self-resolves in 3 to 9 days. 18 In a recent study in people, the prevalence of hyperglycemia was 36%, 24 and no significant difference in age, sex, tumor size, or surgical approach were noted between human patients with normoglycemia and those that were hyperglycemic during the postoperative period. 24 In dogs, postoperative transient hyperglycemia has been commonly recognized, and it has been associated with a better prognosis, 12 whereas the development of permanent DM is believed to be uncommon.…”
Section: Discussionmentioning
confidence: 97%
“…18 In a recent study in people, the prevalence of hyperglycemia was 36%, 24 and no significant difference in age, sex, tumor size, or surgical approach were noted between human patients with normoglycemia and those that were hyperglycemic during the postoperative period. 24 In dogs, postoperative transient hyperglycemia has been commonly recognized, and it has been associated with a better prognosis, 12 whereas the development of permanent DM is believed to be uncommon. 7 In our study, postoperative hyperglycemia was identified in 16 dogs (33%), of which, 7/48 had transient hyperglycemia and 9/48 developed persistent DM.…”
Section: Discussionmentioning
confidence: 97%
“…The blood glucose level occasionally tends to increase after insulinoma resection, a phenomenon known as rebound hyperglycemia [10] which is attributed to atrophy of the remaining pancreatic beta cells [11] or surgically induced pancreatic damage [10]. Our patient showed no signs of rebound hyperglycemia and required infrequent insulin boluses (Fig.…”
Section: Discussionmentioning
confidence: 72%
“…3 In this context, abrupt discontinuation of intravenous insulin led to RH in over 90% of the observed individuals. RH has also been observed in patients without diabetes after resection of insulinomas 4 or after enteral feeding. 5 The use of continuous glucose monitoring (CGM) systems in diabetes management is increasing, and adoption of realtime CGM (rtCGM) systems is associated with sustainable improvements in hemoglobin A1c.…”
Section: Introductionmentioning
confidence: 90%